THE PERCEPTION OF THE CUSTOMS’ STAFF ON ADMINISTRATIVE REFORMS AND TAX COMPLIANCE IN KENYA (International Journal of Innovative Technologies in Economy, 2023)
In developing economies like Kenya, central to the problem of tax compliance are low-income entities, who struggles with making sure they register, file, and pay their taxes on time. All governments, in general, confront the same difficulties in assessing tax compliance risks and adopt administrative reforms, such as system automation, taxpayer education, staff training and enforcement strategies. This study sought to establish how these administrative reforms adopted within the customs offices in Kenya influence tax compliance. The study adopted correlational research design with a target population of 1736 employees within the seven Divisions in Customs & Border Control Department in Kenya. A stratified random sampling technique was applied to identify a sample size of 175 employees for the study. The primary data collected, through questionnaires, was analysed using both descriptive and inferential statistics. The results revealed that the adopted administrative reforms of system automation, taxpayer education, staff training and enforcement strategies explains about 49.1% of the variations on the tax compliance level in Kenya, with system automation, staff training and enforcement strategies having a positive significant influence. Therefore, tax authorities and fiscal policy architects can take proactive steps towards fostering a culture of compliance, thereby enhancing revenue collection and the overall efficiency and effectiveness of tax administration in Kenya.